TINJAUAN YURIDIS TERHADAP FAKTOR DAN DAMPAK PERCERAIAN DI PENGADILAN ( ANALISIS KASUS DI PENGADILAN AGAMA SUBANG - Imam Rahmaddani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Divorce is the best option if every choice and effort has been made to remove the barriers and resolve all these issues but to no avail. Divorce is no longer seen as a taboo lifestyle choice because it is seen as an instant solution to all household problems. In society, divorce is a common thing. The research method used is the data source in the form of primary data in the form of laws and regulations to analyze cases. Meanwhile, secondary data are journals, books, and so on. File documents in the form of the number of cases that were entered at the Subang Religious Court. The purpose of this study is to determine the number of cases, the impact of divorce and the factors that cause divorce. The results of the research are the highest level of divorce cases in the form of contested divorces and talak divorces in the Subang Religious Court. The factors causing divorce to increase in the Subang Religious Court are economic problems, constant fighting, and there is no longer harmony in the household. Keywords: Divorce; Religious courts; Factor; and Impact.